Klasifikasi Jenis Buah Apel Lokal Berdasarkan Penciri Warna, Aspectratio dan GLCM Menggunakan Belt Konveyor Berbasis Raspberry Pi - Lita Nur Fitriani; Fitri Utaminingrum; Wijaya Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Batu City has a variety kind of produce. One of the abundant product of plantations is apples. There are four types of apples, such as Anna Apple, Manalagi Apple, Wanglin Apple, and Rome Beauty Apple. From the four types of apples, when crop is done, and then sorting will be done based on its type, this process still uses human power. Certainly, this process is often inaccurate because the process of selection done can be different for each person. Based on these problems, a sorting system is made by utilizing a classification that can separate the four types of apples based on shape, color, and texture. In this system, it uses a Webcam as a censor to capture images of apples, and then it is processed on Rapberry Pi 3. The process of sorting uses three servos as an actuator to push the apples into its classification. The image that has been captured by the webcam will be processed on Raspberry Pi, and then the image will be done with image processing method to get the Hue, Aspectratio and GLCM Contrast values. If the value has been obtained, Raspberry Pi 3 and Arduino Uno communicate by using I2C serial communication, so that the servo will move based on the result of classification. From the study that has been done, it is obtained the result of the accuracy of aspectratio value as much as 80%. For testing, the accuracy between software and hardware is as much as 80%. While the average time of computation is as much as 159972 ms or 15 seconds.